Bilateral Facial Nerve Palsy: A Diagnostic Dilemma. (23rd January 2012) - Pothiawala, Sohil; Lateef, Fatimah
Abstract : Introduction . Bilateral facial nerve palsy (FNP) is a rare condition, representing less than 2% of all cases of FNP. Majority of these patients have underlying medical conditions, ranging from neurologic, infectious, neoplastic, traumatic, or metabolic disorders. Objective . The differential diagnosis of its causes is extensive and hence can present as a diagnostic challenge. Emergency physicians should be aware of these various diagnostic possibilities, some of which are potentially fatal. Case Report . We report a case of a 43-year-old female who presented to the emergency department with sequential bilateral facial nerve paralysis which could not be attributed to any particular etiology and, hence, presented a diagnostic dilemma. Conclusion . We reinforce the importance of considering the range of differential diagnosis in all cases presenting with bilateral FNP. These patients warrant admission and prompt laboratory and radiological investigation for evaluation of the underlying cause and specific further management as relevant.